ANALISIS MINAT PENGGUNAAN ULANG PADA DOMPET DIGITAL SHOPEEPAY DI MASA PANDEMI COVID-19 - Yola Auralia, (2021)
The purpose of this study is to analyze and prove the influence of perceived usefulness, perceived ease of use and sales promotion on reuse intention the ShopeePay digital wallet during the Covid-19 pandemic. This study is a quantitative research, the data in this research have been acquired form the distribution of questionnaires measured via ascale Likert using the Partial Least Square (PLS) technique which data processing was assisted by Smart PLS 3.3.3. In this research, a sample of 96 people was used, and the sampling technique used was the purposive sampling method. The three variables in this study have an adjusted R-Square value of 0.493 or 49.3% in influencing the reuse intention ofShopeePay digital wallet during the Covid-19 pandemic. Then, the results of this research imply that the perceived usefulness variable has no effect and not significant on interest in reuse with a path coefficient value of 0.192. The variable perceived ease of use has a positive and significant effect on interest in reuse with a path coefficient value of 0.314 and sales promotion has a positive and significant effect on interest in reuse with a path coefficient value of 0.274.